Strategi pengembangan usaha industri rumah tangga bantal dan guling launiya di Desa Ellak Laok, Kecamatan Lenteng, Kabupaten Sumenep - Husain, Abdullah; Suprapti, Isdiana; Hasan, Fuad (Universitas Trunojoyo Madura, 2025)
Home Industry Pillows and Bolsters Launiya is a business of making pillows and bolsters from kapok which is located in Ellak Laok Village, Lenteng District, Sumenep Regency. This research was conducted with the aim of identifying and creating a new business model for Launiya Home Industry in facing business competition by using the Business Model Canvas (BMC) and SWOT analysis. The results of the study show that Launiya Home Industry is in quadrant I or an aggressive growth strategy (Growth oriented strategy) and an alternative strategy for the new BMC proposal where out of 9 elements there are 8 elements of new strategy proposals such as the customer segment component expanding the consumer segment, value proportion adding new product variants and registering business legality, adding website and social media channels, adding key partners such as Tokopedia and Lazada, adding digital marketing key activities, adding key resources for warehouse facilities, sewing machines, HR and clear division of job desks, revenue stream getting additional income from handicrafts which is made from leftover cloth, and the cost structure needs to share the cost of electricity for homes and production activities.